Distributed Port Automata - Krause, Christian (Electronic Communications of the EASST, 2011)
Dynamic reconfigurations are a powerful approach for the adaption of component-based or service-oriented software systems at runtime. Important issues in this area are the problems of state transfer and state consistency, i.e., to determine the system state after a reconfiguration and to ensure that it is valid. To deal with these problems, we introduce distributed port automata in this paper. Distributed port automata combine structural and behavioral system properties and therefore allow to reason about dynamic reconfigurations. In our approach, we use an automata-based model for describing the behavior of the primitive building blocks in a system, and a graph-based model for describing its structure in terms of a network. We demonstrate how to derive the system semantics of a distributed port automaton and show that it is compositional. We consider an encoding of the coordination language Reo and show a new result on compositionality of flattening for distributed graphs.